2019
DOI: 10.3197/np.2019.230102
|View full text |Cite
|
Sign up to set email alerts
|

'(Dis)ordered intensification?' Techno-political models, resource access and pastoralist/agribusiness relations in the Middle Valley of the Senegal River

Abstract: Since the 1990s, the scientific literature has shown how the technical model of intensification of livestock production is ill adapted to the characteristics of semi-arid climates and the pastoral systems operating in them. While this led to changes in the rhetoric of pastoral development, there have been no significant shifts in its conceptual foundations and working methods. This article analyses the forms of this persistence, its effects and its causes in the Valley of the Senegal River through a study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…More generally, the increased number of crossbred and exotic animals is indicative of a shift in production systems toward greater intensification and specialization. This process may impact negatively on landscapes and use of resources, as illustrated by Magnani et al (2019a) . They showed that the sedentarisation of pastoralists and promotion of exotic breeds over local ones resulted in land fragmentation of the middle valley of the Senegal River.…”
Section: Discussionmentioning
confidence: 99%
“…More generally, the increased number of crossbred and exotic animals is indicative of a shift in production systems toward greater intensification and specialization. This process may impact negatively on landscapes and use of resources, as illustrated by Magnani et al (2019a) . They showed that the sedentarisation of pastoralists and promotion of exotic breeds over local ones resulted in land fragmentation of the middle valley of the Senegal River.…”
Section: Discussionmentioning
confidence: 99%